Hubungan antara Ketahanan Pangan Rumah Tangga dengan Peningkatan Berat Badan Ibu Hamil - Syafillah, Irfin Candra; Renda, Belinda Widya; Afifah, Lyna Nur (Media Gizi Kesmas, 2024)
Background: Gestational weight gain (GWG) is one of the predictors associated with birth outcomes. Excessive Gestational Weight Gain (EGWG) associated with post-pregnancy obesity nutritional status in the long term. GWG related by various factors, one of which is household food security status. Objectives: The study aimed to analyze the relationship between food security and GWG. Methods: This study used a case-control study design with 54 pregnant women who were divided into a case group (27 respondents with EGWG) and a control group (27 respondents with normal GWG). Pregnant women were interviewed using a general questionnaire and Food Insecurity Experience Scale (FIES) questionnaire for household food security status. The chi square and the odds ratio test were carried out to assess the relationship between the independent variables, food security and GWG Results: The results showed that one of the indicators of individual characteristics, pre-pregnancy Body Mass Index (BMI), had a relationship with GWG (p=0.029; OR = 4.038; 95% CI: 1.295-12.585). One indicator of socio-economic characteristics, employment status also had a significant relationship with GWG (p=0.029; OR = 4.156; 95% CI: 1.312-13.169). Food security status was found not to be associated with GWG (p=0.743). Conclusions: Efforts to prevent EGWG in this population can focus on early identification, pre-pregnancy BMI and other risk factors such as employment status. Another aspect studied, food security, was found to have no relationship with GWG.